POSSIBILITIES FOR SUPPORTING THE DEVELOPMENT OF CHILDREN DISLIKED BY PEERS DUE TO ANTI-SOCIAL BEHAVIOUR - Herzberg, Marta (The Modern Higher Education Review, 2021)
The article presents the theoretical foundations of an interaction program addressed to children who are disliked by their peers from the school class due to their anti-social behaviour. The program is addressed to students aged 10-11, and its aim is to create conditions for participants to develop emotional self-control, interpersonal decentration and formation of their self-esteem. The quality of the program is evidenced by the changes that occurred in children participating in the activities compared to children in the control group. The program is an example of selective prevention, the actions of which are targeted at high-risk groups exposed to social maladjustment and emotional disorders in adolescence and adulthood.